PENGARUH MODEL CREATIVE PROBLEM SOLVING BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA Fase E SMA PEMBANGUNAN LABORATORIUM UNP - Rifqi Wahyu Rizaldi; Yerizon (Smart Education, 2026)
Abstract: Mathematical problem-solving skills (KPPM) are one of the essential skills for students in the 21st century. However, in reality, these skills among Phase E students at UNP Pembangunan Laboratorium High School remain low. One instructional model considered effective in addressing this issue is the Creative Problem Solving with GeoGebra (CPS) model. The purpose of this study is to describe the development of students’ mathematical problem-solving skills during the learning process using the CPS model with the aid of GeoGebra, as well as to determine whether there is a difference in outcomes compared to students who participate in traditional, technology-free instruction. This study employs a quasi-experimental design and a descriptive analysis using a non-equivalent post-test-only control group design. The population for this study consisted of Phase E students for the 2025/2026 academic year at UNP Pembangunan Laboratorium High School. The sample was selected using simple random sampling, with class X E3 serving as the experimental class and class X E2 as the control class. The instruments used were quizzes and the KPMM test. The results of the analysis showed an increase in students’ KPMM scores in the experimental class, and the results of the hypothesis test indicated that students taught using the CPS model aided by GeoGebra performed better than those using the direct instruction model in solving mathematical problems. Keywords: Mathematical Problem Solving Ability; Creative Problem Solving; GeoGebra. Abstrak: Kemampuan pemecahan masalah matematis (KPMM) ialah salah satu kemampuan yang penting dimiliki siswa di abad 21. Namun, kenyataannya kemampuan tersebut pada siswa Fase E di SMA Pembangunan Laboratorium UNP masih rendah. Salah satu model pembelajaran yang dinilai efektif dalam mengatasi permasalahan tersebut yaitu model Creative Problem Geogebra (CPS). Tujuan penelitian ini untuk menggambarkan perkembangan KPPM siswa dalam proses pembelajaran yang menggunakan model CPS dengan bantuan GeoGebra, serta untuk mengetahui apakah ada perbedaan hasilnya dengan siswa yang mengikuti pembelajaran langsung dan tanpa teknologi. Penelitian ini menggunakan desain kuasi eksperimen dan kajian deskriptif dengan non-equivalent post test only control group design. Siswa Fase E tahun ajaran 2025/2026 dari SMA Pembangunan Laboratorium UNP menjadi populasi penelitian ini. Sampel diambil menggunakan teknik simple random sampling, dengan X E3 menjadi kelas eksperimen dan X E2 menjadi kelas kontrol. Instrumen yang digunakan kuis dan tes KPMM. Hasil analisis memperlihatkan terdapat peningkatan KPMM siswa di kelas eksperimen, serta hasil uji hipotesis mengindikasikan bahwa kemampuan siswa yang pembelajarannya dengan model CPS berbantuan GeoGebra lebih baik dari siswa yang menggunakan model pembelajaran langsung dalam memecahkan masalah matematika. Kata kunci: Kemampuan Pemecahan Masalah Matematis; Creative Problem Solving; GeoGebra.